Children who leave the emergency department without being seen: a retrospective case note review. Issue 9 (2nd December 2014) - Sparrow, Nicola; Pestell, Trudie; Clancy, Mike
Abstract : Introduction: Children who attend an emergency department and then leave without being seen (LWBS) are a major concern as they are a potentially vulnerable group who may come to harm through failure to provide a timely and accessible service. Objectives: We wished to establish the size of this population and importantly what subsequently happened to them over the following 7 days from their initial attendance, and the relevance of the College of Emergency Medicine LWBS Quality Indicator (QI 4) to this group. Methods: A retrospective case note review over 6 months of all paediatric attendances who LWBS. Setting: Southampton Paediatric Emergency Department. Results: During a 6-month study period, 10 795 attended, of which 544 (5%) LWBS. 12.6% (69/544) reattended over the next 7 days, of which 14 were admitted, 7 for <12 h. Conclusions: The majority who LWBS do so during peak times. Very few paediatric patients who LWBS then reattended required admission for >12 h (7/544, 1.3%). The rate of reattendance of those who LWBS and review of their case notes is potentially more valuable than the LWBS rate alone.